Artesunate Induces ROS-Mediated Apoptosis in Doxorubicin-Resistant T Leukemia Cells - Efferth, Thomas; Giaisi, Marco; Merling, Annette; Krammer, Peter H.; Li-Weber, Min (PLOS ONE, 2007)
BackgroundA major obstacle for successful cancer treatment often is the development of drug resistance in cancer cells during chemotherapy. Therefore, there is an urgent need for novel drugs with improved efficacy against tumor cells and with less toxicity on normal cells. Artesunate (ART), a powerful anti-malarial herbal compound, has been shown to inhibit growth of various tumor cell lines in vitro and of xenografted Kaposi's sarcoma in mice in vivo. However, the molecular mechanisms by which ART exerts its cytotoxicity have not been elucidated. The ART-class of anti-malarial compounds is attractive due to their activity against multidrug-resistant Plasmodium falciparum and Plasmodium vivax strains. Another salient feature of these compounds is the lack of severe side effects in malaria patients.Methodology and Principal FindingsIn this study, we used T-cell leukemias as a model system to study the molecular mechanisms of ART-induced apoptosis. The most typical anticancer drugs are DNA intercalators such as Doxorubicin. To investigate drug sensitivity and resistance, we chose a Doxorubicin-resistant leukemia cell line and investigated the killing effect of ART on these cells. We show that ART induces apoptosis in leukemic T cells mainly through the mitochondrial pathway via generation of reactive oxygen species (ROS), a mechanism different from Doxorubicin. This is confirmed by the fact that the antioxidant N-Acetyle-Cysteine (NAC) could completely block ROS generation and, consequently, inhibited ART-induced apoptosis. Therefore, ART can overcome the Doxorubicin-resistance and induce the Doxorubicin-resistant leukemia cells to undergo apoptosis. We also show that ART can synergize with Doxorubicin to enhance apoptotic cell death in leukemic T cells. This synergistic effect can be largely explained by the fact that ART and Doxorubicin use different killing mechanisms.ConclusionsOur studies raise the possibility to develop ART in combination with other established anticancer drugs which induce apoptosis through the pathways or mechanisms different from ART.